2017
DOI: 10.1186/s12891-017-1593-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between Epicondylitis and Cardiovascular Risk Factors in Pooled Occupational Cohorts

Abstract: BackgroundThe pathophysiology of lateral epicondylitis (LE) is unclear. Recent evidence suggests some common musculoskeletal disorders may have a basis in cardiovascular disease (CVD) risk factors. Thus, we examined CVD risks as potential LE risks.MethodsWorkers (n = 1824) were enrolled in two large prospective studies and underwent structured interviews and physical examinations at baseline. Analysis of pooled baseline data assessed the relationships separately between a modified Framingham Heart Study CVD ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…In their study of 1824 workers across multiple domains, Hegmann et al (2017) not only found that those with CVD risk factors had 6 times higher risk of epicondylitis, but also identified literature showing similar risk levels for other musculoskeletal conditions, such as carpal tunnel syndrome (5 times higher in those with CVD markers), median nerve entrapment (8 times higher in those with CVD risk factors) and rotator cuff tendinopathy. The presence of diabetes in workers was also found to increase likelihood of epicondylalgia.…”
Section: Central Sensitivity and Allostatic Loadmentioning
confidence: 93%
See 3 more Smart Citations
“…In their study of 1824 workers across multiple domains, Hegmann et al (2017) not only found that those with CVD risk factors had 6 times higher risk of epicondylitis, but also identified literature showing similar risk levels for other musculoskeletal conditions, such as carpal tunnel syndrome (5 times higher in those with CVD markers), median nerve entrapment (8 times higher in those with CVD risk factors) and rotator cuff tendinopathy. The presence of diabetes in workers was also found to increase likelihood of epicondylalgia.…”
Section: Central Sensitivity and Allostatic Loadmentioning
confidence: 93%
“…For example, diabetes is well known to contribute to the atherosclerotic process. Since connective tissues are poorly supplied by vasculature, their tolerance for compromise is narrowed (Hegmann et al, 2017). Similarly, type 2 diabetics have an over-abundance of circulating insulin due to cellular resistance to insulin.…”
Section: The Stress Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, while this study found an increased risk of CAD in patients with a previous diagnosis of CTS, it remains unclear as to whether other neuromuscular diseases or symptoms may also be related to CAD. Previous research has confirmed that rotator cuff tendinopathy [ 42 ] and lateral epicondylitis [ 43 ] are related to the development of CAD, although it remains uncertain as to whether the mechanisms leading to the development of CAD are similar between these neuromuscular diseases and CTS. Importantly, the scope of our research is limited by the fact that some symptoms or signs cannot be diagnosed as a disease relating to a specific ICD-9-CM code.…”
Section: Discussionmentioning
confidence: 99%